ESSENTIAL EXTENSION OF TOPOLOGICAL GROUPS - Majeed, Taghreed Hur (MAGISTRA, 2015)
Our principle aim is to study an algebraic group properties topologically and specially essential extension of topological groups. Among the results in paper are obtained. We show how you can find extension and essential of topological groups by other given topological group. Furthermore, new proposition (as we know) are given at the end of this work. Key Words: Injective topological group, essential extension of topological group, topological group, direct sum.